Marine Algae of Sert Coasts, Libya - Godeh, Massoud; Said, Alaa; El-Menifi, Fathalla; Zarmouh, Meftah (Libyan Journal of Science &Technology, 2022)
The present work was mainly intended to make recent data base of marine algae population at Sert coasts as a first step to evaluate some of their chemical composition, antimicrobial activities and economic importance. Collection, identification and classification of marine algae of Sert coasts at Mediterranean Sea eastern Tripoli were done through some irregular visits during 2008 and 2009. A total of 21 algal species (21 genera) were recorded at the study area. Five species of them (23.81%) were belonging to Chlorophyta (5 families), Six species (28.57%) belonging to Phaeophyta (4 families) and Ten species (47.62%) belonging to Rhodophyta (4 families) with special reference to Cystoseiraceae and Dityotaceae families of Phaeophyta and Corallinaceae and Rhodomelaceae families of Rhodophyta. Most of the recorded algae were safely edible and still needed to know more about their chemical composition and antimicrobial activity.